Clothing of migrant Muslim women in Taguig, Metro Manila - Bongyad, Odessa Sanchez; Elumba, Patricia Santos (2002.)
The Muslim woman's dress seems to receive more attention in society than most attire. Many people have no idea or perspective of their manner of dressing and the tendency is to focus more on the Muslim woman herself. The idea for this research was brought about by the so-called change in the practice of migrant Muslim women and their children who no longer wear their traditional Muslim clothes publicly. The study attempted to know the clothing adopted by Muslim women in conforming with the conditions they have encountered in their new environment. The researcher will try give clear picture of the socio, economic and educational profile of the migrant Muslim women. She will also evaluate and to look at the changes and the manner of clothing of the migrants, their clothing decisions in choosing their clothes, clothing values, present owned garment sample, the levels and lengths of their present dress and lastly, the different problems they have encountered in wearing their traditional clothes in Metro Manila. In general, a descriptive-normative survey technique was utilized to collect the data. There are 170 migrant women in Maharlika Village in Taguig, Metro Manila who were asked to represent or serve as samples of the study because of the highly concentrated migrant Muslim population in this place. All of them belong to three major ethno-linguistic groups: Tausug, Maguindanao and Maranao. The collection of data was conducted within the last week of January and the first week of March year 2002. Respondents who are covered in the survey are believed to share similar clothing attributes and perceptions with the rest of the Muslim women in their affiliated group due to homogeneity within each stratum. There are four statistical techniques that were employed to answer the objectives of the study. The data results show that almost three-fourths of the migrant Muslim women have changed in the manner of their clothing upon migrating here in Metro Manila, but only to some extent. Their length of stay in Maharlika Village, age, educational background and their income do not affect the change in their dressing. Only their religious affiliation is strongly associated with their attire. Even if there are certain changes that happened to them, they or majority still dress up in a fairly conservative manner. Although some of them dress in the unconventional Muslim attire, most of them still prefer to clothe themselves in long type of dresses. There are strong forces like one's parents in terms of the decision they make in choosing their clothes. However, their friends are their number one inspiration on how they are going to dress up. When it comes to choosing their own style of dress, they consider the aesthetic value and color of their skin before actually buying certain types of dresses in malls. The quality of clothes was the top consideration in their clothing purchase-decisions. Most of them prefer light color dresses. Thus, they see to it that clothes are economically affordable. They do not spend so much for their clothes because food is more important to them.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Islamic clothing and dress